Hao Si Bu Ru Lai Huo Zhe . To Live is Better than to Die - Weijun, Chen (China, 2003)
Duration: 01:00:00 In the 1990s, around 100,000 subsistence farmers in central China were offered a rare opportunity to earn some extra income. Through a state-organized program, they could sell their blood for money. However, due to the poor conditions of the state hospital, over half of those giving blood were infected with the HIV virus. In the beginning of 2001, director Chen Weijun went to the village of Wenlou, which had come to the world‘s attention because of the number of its infected citizens. In a cinéma vérité style he captures the tragic fate of a family with three small children, in which only the eldest sister was able to escape the deadly disease.